Investigating mechanisms underpinning the detrimental impact of a high-fat diet in the developing and adult hypermuscular myostatin null mouse. Issue 1 (December 2015) - Matsakas, Antonios; Prosdocimo, Domenick; Mitchell, Robert; Collins-Hooper, Henry; Giallourou, Natasa; Swann, Jonathan; Potter, Paul; Epting, Thomas; Jain, Mukesh; Patel, Ketan
Abstract Background Obese adults are prone to develop metabolic and cardiovascular diseases. Furthermore, over-weight expectant mothers give birth to large babies who also have increased likelihood of developing metabolic and cardiovascular diseases. Fundamental advancements to better understand the pathophysiology of obesity are critical in the development of anti-obesity therapies not only for this but also future generations. Skeletal muscle plays a major role in fat metabolism and much work has focused in promoting this activity in order to control the development of obesity. Research has evaluated myostatin inhibition as a strategy to prevent the development of obesity and concluded in some cases that it offers a protective mechanism against a high-fat diet. Methods Pregnant as well as virgin myostatin null mice and age matched wild type animals were raised on a high fat diet for up to 10 weeks. The effect of the diet was tested on skeletal muscle, liver and fat. Quantitate PCR, Western blotting, immunohistochemistry, in-vivo and ex-vivo muscle characterisation, metabonomic and lipidomic measurements were from the four major cohorts. Results We hypothesised that myostatin inhibition should protect not only the mother but also its developing foetus from the detrimental effects of a high-fat diet. Unexpectedly, we found muscle development was attenuated in the foetus of myostatin null mice raised on a high-fat diet. We therefore re-examined the effect of the high-fat diet on adults and found myostatin null mice were more susceptible to diet-induced obesity through a mechanism involving impairment of inter-organ fat utilization. Conclusions Loss of myostatin alters fatty acid uptake and oxidation in skeletal muscle and liver. We show that abnormally high metabolic activity of fat in myostatin null mice is decreased by a high-fat diet resulting in excessive adipose deposition and lipotoxicity. Collectively, our genetic loss-of-function studies offer an explanation of the lean phenotype displayed by a host of animals lacking myostatin signalling.